Cover Feature: Surfactant‐Mediated and Morphology‐Controlled Nanostructured LiFePO4/Carbon Composite as a Promising Cathode Material for Li‐Ion Batteries (ChemistryOpen 1/2020). Issue 1 (27th December 2019) - Khan, Sourav; Raj, Rayappan Pavul; George, Laurel; Kannangara, G. S. Kamali; Milev, Adriyan; Varadaraju, Upadhyayula V.; Selvam, Parasuraman
Abstract : The Cover Feature shows morphology‐controlled in‐situ carbon‐coated nanostructured LiFePO4 (LFP/Carbon) cathode materials prepared by surfactant‐assisted hydrothermal method using block copolymers such as Pluronic® P31R1 and Pluronic® P123. The resulting nanocrystalline high surface area materials show superior properties and were designated as LFP/C123 and LFP/C311, respectively. Further, the latter demonstrated outstanding electrochemical performance in terms of lower charge transfer resistance (146.3 Ω) with excellent cycling stability in terms of capacity retention (95% at 1 C after 100 cycles) and high rate capability (163.2 mAhg‐1 at 0.1 C). More information can be found in the Full Paper by Dr. G. S. Kamali Kannangara et al. on page 24 in Issue 1, 2020 (DOI: 10.1002/open.201900175 ).